PEMENUHAN HAK PEKERJA PERJANJIAN KERJA WAKTU TERTENTU YANG MELAMPAUI JANGKA WAKTU (STUDI KASUS PT. ASIA OUTSOURCING SERVICES) - Khairany Azahra, (2022)
Certain Time Work Agreements have been determined by law, however, there are still agreements that exceed the time period which causes problems related to the legal status of Certain Time Work Agreements and legal consequences related to Certain Time Work Agreements. The purpose of this study is to describe descriptively related to outsourcing practices in accordance with the Manpower Act. The results of this study indicate that the legal status of PKWT that exceeds the period of a certain time work agreement between the worker and the company PT Asia Outsourcing Services is that the PKWT Contract Status violates the rules so that the status of the employee should have become PKWTT and the legal consequences of PKWT must be in accordance with the laws that regulate the term of the agreement may not exceed 3 years, so that PT Asia Outsourcing Services applies the PKWT system successively, then PT Asia Outsourcing Services violates the rules, this is because the company extending the PKWT exceeds the period of time with workers continuously then it not allowed. has been stipulated, namely Law Number 13 of 2003 concerning Manpower. There needs to be a comprehensive socialization effort regarding the legislation related to the legal status of PKWT that exceeds the time period, due to the lack of socialization regarding PKWT provisions so that it can harm employees.